Physiological analysis of cognitive load variations during complex information processing - Allan Armougum; Alexandre Gaston-Bellegarde; Chantal Joie-La Marle; Pascale Piolino (European Transport Research Review, 2025)
Abstract Information processing in complex contexts generates higher cognitive demand than in optimal contexts. Though information processing is cognitively less demanding in experts, due to their high level of prior knowledge and considerable number of schemas, a rise in the information complexity in non-optimal context could generate an expertise reversal effect. In our study, we analysed how incidental presentation of information affects cognitive load of train travellers with different expertise levels during navigation in an immersive virtual train station. Analyses of electroencephalography and electrodermal activities as physiological metrics, NASA-Task Load Index as subjective measure and binding memory score as behavioural measure of performance during a recognition phase, helped to quantify cognitive load during the study. With rise in expertise of the investigated train station, participants showed equal or higher cognitive load than participants with lower expertise level, from encoding to recognition phase of the experiment, suggesting an expertise reversal effect. Participants with less expertise did not show any statistically significant difference in cognitive load level from encoding to recognition phase. These findings suggest that complex environmental contexts could contribute to reduce schemas update with increasing expertise level, generating expertise reversal effect.